ASPEK KELEMBAGAAAN BAITUL MAAL WA TAMWIL YANG BELUM MENDAPAT IZIN USAHA DARI OTORITAS JASA KEUANGAN DAN AKIBAT HUKUMNYA TERHADAP KEGIATAN PENGHIMPUNAN DANA: Studi Kasus di KSPPS BMT El Bummi - Dzulhijjah, Liza; Rohmah, Tuthi Mazidatur; Nurhayati, Irna (Khatulistiwa Law Review, 2020)
This research departs from the gap between the provision in Act Number 1 of 2013 concerning Micro Finance Institution (Micro Finance Institution Act) and its implementation. Article 39 Micro Finance Institution Act states that Baitul Maal wa Tamwil (BMT) is one of Micro Finance Institution which is required to obtain a business permit from OJK maximum 1 year after Micro Finance Institution Act has been applied, but in its implementation on August 2019, there is no BMT in Yogyakarta which obtained a business permit as Micro Finance Institution from OJK even though the amount of BMT in Yogyakarta which registered as Sharia Cooperation (KSPPS) reached 126 unit, one of them is KSPPS BMT El Bummi. This research focused on the institutional aspect of BMT and its legal consequences for fundraising and legal protection of members and society as depositors.